A novel heterozygous variant p.(Trp538Arg) of SYNM is identified by whole‐exome sequencing in a Chinese family with dilated cardiomyopathy. (2nd October 2018) - Zhang, Shu‐Bing; Liu, Yu‐Xing; Fan, Liang‐Liang; Huang, Hao; Li, Jing‐Jing; Jin, Jie‐Yuan; Xiang, Rong
Abstract: Dilated cardiomyopathy (DCM) is a relatively frequent myocardial disease that may lead to heart failure, syncope, and sudden cardiac death. Genetic factors play important roles in the etiology of the disease. To date, at least 50 genes have been identified in patients with DCM, among them, only three mutations have been reported in Synemin ( SYNM ) gene. In this study, we investigate a Chinese family of three generations with four patients with DCM. Employing whole‐exome sequencing (WES) and bioinformatics strategies, a novel heterozygous missense mutation p.(Trp538Arg) of SYNM was identified and cosegregated with the affected family members. The missense mutation locates in the C‐terminal domain of SYNM and leads to a substitution of tryptophan by arginine and may cause the structure change of synemin protein. In conclusion, we employed WES to detect the mutations of DCM patients and identified a novel likely pathogenic mutation in SYNM gene. Our study not only expands the spectrum of SYNM mutations, it further confirms that mutations in SYMN may underlie nonfamilial DCM, and offers genetic testing information to additional DCM patients.